Development Of Hots-Based Assessment in the Curriculum to Increase Critical Thinking Skills of Elementary School Students - Yusella, Yeni; Suciptaningsih, Oktaviani Adhi; Degeng, Made Duananda Kartika (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2023)
HOTS is an important aspect of learning. Higher order thinking skills are the process of analyzing, reflecting, giving arguments (reasons), applying concepts to different situations, and creating. Given the importance of the HOTS position in learning, teachers need to have knowledge and competencies that can help in developing the higher-order thinking skills of their students. This study aims to develop a qualified HOTS-based assessment instrument so that elementary school teachers can use it to develop students' thinking skills. This research is a research and development with the stages of the ADDIE model: (1) Analyze, (2) Design, (3) Develop, (4) Implement, and (5) Evaluate. The results of this study show that the HOTS-based assessment instrument developed for fifth grader is valid, practical, and reliable so that it is suitable for use in training fifth grader to do HOTS-based questions. The validation results of material experts and linguists show that the HOTS-based assessment instrument developed is valid.